A Systematic Literature Review on the Effectiveness of Psychoeducational Interventions for Anxiety and Depression - Yoga Cahya Pangesta; Rahadatul Aissy; Muslikah Muslikah (CV. Ulil Albab Corp, 2026)
Anxiety and depression are global mental health challenges that require preventive and accessible interventions. This study aims to evaluate the effectiveness of psychoeducational interventions for anxiety and depression. The method used was a Systematic Literature Review (SLR) following the PRISMA protocol, analyzing 12 international empirical articles (2016–2026) obtained from the ScienceDirect, Sage, Taylor & Francis, and Wiley databases. The review results indicate that psychoeducation effectively reduces cognitive distortions, automatic thoughts, and improves depression literacy and psychological well-being, among clinical patients, students, and family caregivers. This intervention has proven to be flexible, capable of being delivered through both in-person formats and self-directed digital platforms with comparable outcomes. However, its effectiveness is influenced by the duration of the intervention, sociocultural barriers, societal stigma, and the complexity of the subjects’ conditions. The study’s conclusions affirm that psychoeducation is an adaptive and flexible method for improving mental health literacy and self-efficacy. The novelty of this study lies in its comprehensive synthesis of the transformation of digital psychoeducation as a solution for expanding access to integrated mental health services